EVALUASI KINERJA MELALUI PENDEKATAN BALANCE SCORECARD: FOKUS PADA KEPUASAN DAN KESEJAHTERAAN KARYAWAN PADA PERUSAHAAN XYZ - Erma Widyastuti; Nisrina Akbar Rizky Putri (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to evaluate the performance of XYZ Company using the Balanced Scorecard (BSC) approach, which emphasizes four main perspectives: financial, customer, internal business processes, and learning and growth. The research focuses on employee satisfaction and well-being as key factors in supporting organizational performance improvement. A quantitative research method was applied using a survey with questionnaires distributed to 100 employees. The collected data were analyzed through validity and reliability tests as well as multiple linear regression analysis. The results indicate that XYZ Company has an overall good performance, with the highest score in the learning and growth perspective (4.3), reflecting excellent employee satisfaction and well-being. The financial (4.1) and customer (4.2) perspectives also showed good results, while the internal process perspective requires further improvement (3.9). Regression analysis revealed that employee satisfaction and well-being have a significant positive effect on company performance, contributing 68%. Therefore, the implementation of the Balanced Scorecard provides a comprehensive overview of organizational performance while highlighting the importance of managing employee well-being as a strategic approach to enhancing long-term competitiveness. Keywords: Balanced Scorecard, Employee Satisfaction, Employee Well-being, Company Performance